1988
DOI: 10.1159/000138441
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Sennosides on Uterine Motility in the Pregnant Ewe

Abstract: The effects of sennosides on uterine motility were evaluated by electromyography in healthy adult ewes between day 70 and 120 of pregnancy to assess possible disturbances of the physiological pattern of contractility and eventual risks in pregnancy maintenance. At this stage of pregnancy, the ovine genital tract presented motility episodes of 6–8 min duration occurring at approximately hourly intervals. A dose-range study (10–160 mg/kg intracolonically) in 2 ewes showed that diarrhea was systematically obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
(17 reference statements)
1
1
0
2
Order By: Relevance
“…After pretreating rats with sennosides we registered a decrease in contractility of the isolated uterus which resembles the outcome of experiments in pregnant ewes [8], On the contrary, the studies in isolated rat uterus showed no change in contractions unless the bath solution of rhein-Na was augmented to extreme concentrations of 3 X 10~4 mol/1 or higher. In spite of the difficulties known for calculating the unstable patterns of more or less rhythmic contractions in isolated uter ine tissue, the impression prevails that it was an unspecific irritation of the tissue by rheinNa which enhanced contractility.…”
Section: Discussionsupporting
confidence: 73%
“…After pretreating rats with sennosides we registered a decrease in contractility of the isolated uterus which resembles the outcome of experiments in pregnant ewes [8], On the contrary, the studies in isolated rat uterus showed no change in contractions unless the bath solution of rhein-Na was augmented to extreme concentrations of 3 X 10~4 mol/1 or higher. In spite of the difficulties known for calculating the unstable patterns of more or less rhythmic contractions in isolated uter ine tissue, the impression prevails that it was an unspecific irritation of the tissue by rheinNa which enhanced contractility.…”
Section: Discussionsupporting
confidence: 73%
“…Der Übertritt von Sennosiden in die Muttermilch ist minimal, die kindlichen Stühle werden nicht weicher [242][243][244]. Aborte werden nicht begünstigt [245,246]. Die oft behauptete Gewöhnung an Sennoside scheint sehr selten zu sein, systematische Untersuchungen hierzu fehlen jedoch.…”
Section: Kommentarunclassified
“…The abortifacient effects related to the use of medicinal plants in pregnancy, are also reported in the literature [4,[21][22][23][28][29][30][31][32]. As example of the abortifacient plants are: Senna alexandrina Mill (Fabaceae) (sene) [4,30,33,[35][36][37], Rhamnus purshiana DC (Rhamnaceae) and Rhamnus catharticus (Rhamnaceae) (cáscara-sagrada) [4,30,31,37], Mentha pulegium L. (Lamiaceae) (poejo) [4,[38][39][40], Mentha arvensis L. (Lamiaceae) (hortelã-japonesa) [4,41], Chenopodium ambrosioides L.…”
Section: Perception Of Health Risksmentioning
confidence: 99%